Cross sectional study of bovine and avian tuberculosis in Bangladesh Livestock Reasearch Institute (BLRI) cattle farm - Biswas, Prokash; Rahman, Md Bahanur; Sharmy, Sayra Tasnin; Khan, Md Ferdousur Rahman; Rahman, Md Mizanur; Moniruzzaman, Mohammad; Alam, Md Emtiaj; Rahman, Md Siddiqur (Asian Journal of Medical and Biological Research, 2017)
The present study was carried out to determine the prevalence of bovine and avian tuberculosis in cattle by using bovine and avian PPDs at Bangladesh Livestock Research Institute (BLRI) Cattle Farm, Savar, Dhaka. Cattle of different breeds, ages and sexes (n=183) were tested using bovine and avian PPDs. In caudal Fold Tuberculin (CFT) test, 16 (8.74%) cases were showed positive reaction among 183 sample. The overall percentages of positive reactors to Comparative cervical tuberculin (CCT) test of bovine and avian tuberculosis were 7.10% and 1.64% respectively. An insignificant variation (P>0.05) on prevalence of bovine tuberculosis on different age group of cattle was observed. Age group >7 years showed a higher prevalence (10.91%) than those of other age groups. In CCT test, 7.55% and 4.17% positive reactors were found in female and male cattle respectively. The association between different breeds of the animal was found significant (P<0.05). The local breed showed higher prevalence (9.77%) than those of Red Chittagong and cross breed. The highest percentage (10.45%) of positive reactors in CCT test was recorded in milking cows than in dry cows (2.32%), heifer (9.52%) and calf (5.77%) were observed. Mixed infection (bovine and avian type of tuberculosis) was recorded 1.64%. Asian J. Med. Biol. Res. September 2017, 3(3): 352-356